The Impact of Burnout, Work Environment, and Work Motivation on Employee Productivity: Evidence - Danila Putriyana; Aris Wahyu Kuncoro (Golden Ratio of Data in Summary, 2026)
This study aims to examine the impact of burnout, work environment, and work motivation on employee productivity at PT Yuasa Industrial Battery Indonesia. Employing a descriptive quantitative design, this research used a saturated sampling technique involving all 53 employees of the company as respondents. Data were analyzed using multiple linear regression to assess the individual and simultaneous effects of the variables. The results indicate that burnout has no significant effect on employee productivity (p > 0.05), whereas both work environment and work motivation show positive and significant effects (p < 0.05). The model explains 58.8% (R² = 0.588) of the variation in employee productivity. These findings align with Herzberg’s Two-Factor Theory, emphasizing that intrinsic and extrinsic motivators are key drivers of performance. The insignificance of burnout suggests the presence of possible mediating factors such as job satisfaction or organizational culture. The study’s originality lies in its empirical evidence from Indonesia’s battery manufacturing sector, contributing to the human resource management literature by integrating psychological and environmental dimensions of productivity. Practically, the results imply that companies should prioritize supportive work environments and motivation-enhancing strategies to sustain high employee performance and organizational competitiveness.